2019
DOI: 10.1039/c9fd00041k
|View full text |Cite
|
Sign up to set email alerts
|

Direct experimental evaluation of ligand-induced backbonding in nickel metallacyclic complexes

Abstract: The details of ligand-induced backbonding in nickel diphosphine π complexes are explored using nickel L-edge (3d←2p) X-ray absorption spectroscopy as a means of quantifying the degree of backbonding derived from direct Ni 3d donation into the π ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This geometry is a result of electron donation from the bisphosphine ligand into the 3d(x 2 -y 2 ) orbital, which is also engaged in d to p* backbonding. 32,33 The measured K eq for the displacement of COD from 1 using benzaldehyde (>20), benzophenone (0.65), and acetophenone (0.02) are sufficiently large that under catalytic conditionsi.e. in the presence of a large excess (ca.…”
Section: Resultsmentioning
confidence: 99%
“…This geometry is a result of electron donation from the bisphosphine ligand into the 3d(x 2 -y 2 ) orbital, which is also engaged in d to p* backbonding. 32,33 The measured K eq for the displacement of COD from 1 using benzaldehyde (>20), benzophenone (0.65), and acetophenone (0.02) are sufficiently large that under catalytic conditionsi.e. in the presence of a large excess (ca.…”
Section: Resultsmentioning
confidence: 99%
“…Aldehydes and ketones are known to be excellent ligands for low valent nickel complexes, [40][41][42][43] with nickel complexes that bear a bidentate phosphine ligand (typically dtbpe) giving rise to some interesting electronic effects that have been examined in detail by Kennepohl and Love (dtbpe = 1,2-di(tert-butylphosphino)ethane). 44,45 Amides and esters did not benefit from this coordination effect. In the reaction between [Ni(COD)(dppf)] and 4-chlorobenzaldehyde, an intermediate was observed that presented two doublets in the 31 P NMR spectrum; these were attributed to the η 2 (CO)complex.…”
Section: Reactions With Aryl Halidesmentioning
confidence: 93%
“…Electron donation from the methyl group into the valence Ni 4px causes a slight increase in the energy of the metal valence orbitals. 46,47 We note that Pauli repulsion with the agostic methyl group is also expected to raise the energy of the 3d←2p feature.…”
Section: Td-dft Calculations and Simulation Of Ni K Edge Xasmentioning
confidence: 87%